Research Of The Institutes In The Period Of Changes. About Summer School «Institutional Dynamics In Mind Of Economists And Sociologists», July 4-8, 2008 - КрыловДмитрий Александрович (Journal of Economic Sociology, 2010)
Detailed description in the text